Docile Bodies in Chinese Schools: What Defines a Future Postmodern Education? - Li, Yulong (Critical Education, 2022)
As early as the 1990s, educationists, and even some governmental policy makers in China, advocated suzhi (quality) educational reform, aiming to develop creative individuals, and to revamp the exam-oriented and authoritarian education system. However, this suzhi educational reform was not entirely successful, with education in China becoming a hybrid of suzhi coupled with the much-maligned authoritarian and exam-oriented system. I believe that students’ quotidian life at school is governed by a disciplinary power that imposes a hidden curriculum. This essay uses Foucault’s major theories as a conceptualizing framework by examining the control of time, space, and body etc. as technologies of power at Chinese primary and secondary schools. The study concludes by depicting a postmodern future for Chinese students in which they flourish with creativity and innovation.